Advances in dendritic cell targeting nano-delivery systems for induction of immune tolerance - Lin, Guojiao; Wang, Jialiang; Yang, Yong-Guang; Zhang, Yuning; Sun, Tianmeng (Frontiers in Bioengineering and Biotechnology, 2023)
Dendritic cells (DCs) are the major specialized antigen-presenting cells (APCs), play a key role in initiating the body's immune response, maintain the balance of immunity. DCs can also induce immune tolerance by rendering effector T cells absent and anergy, and promoting the expansion of regulatory T cells. Induction of tolerogenic DCs has been proved to be a promising strategy for the treatment of autoimmune diseases, organ transplantation, and allergic diseases by various laboratory researches and clinical trials. The development of nano-delivery systems has led to advances in in situ modulation of the tolerance phenotype of DCs. By changing the material composition, particle size, zeta-potential, and surface modification of nanoparticles, nanoparticles can be used for the therapeutic payloads targeting delivery to DCs, endowing them with great potential in the induction of immune tolerance. This paper reviews how nano-delivery systems can be modulated for targeting delivery to DCs and induce immune tolerance and reviews their potential in the treatment of autoimmune diseases, organ transplantation, and allergic diseases.